"Doomed to a kind of double consciousness": treacherous hospitality and the inversion of tradition in A.S. Byatt's "Morpho Eugenia". (1st September 2020) - Gefter Wondrich, Roberta
ABSTRACT: A.S. Byatt's "Morpho Eugenia" marks a significant moment in the consideration of (narrative) hospitality in neo-Victorian fiction. It expands on the concerns of neo-Victorianism by foregrounding the theme of hospitality in discourses that are central to the Victorian novel and to contemporary re-interpretations of Victorian culture. Among these are the trope of the visit to the family house in the English novel, in which guests are often then assimilated into the family, and the perils and threats to personal identity that come with the crossing of the threshold of hospitality. A third is the relationship with the 'other' in the un/conditional hospitality that is experienced by the protagonist. All of these sub-themes are contained in an epistemological dimension defined by science and religion, problematically interrelated at the time. This article thus considers the conceptual standpoint and the narrative strategies with which Byatt engages with the literary tradition of hospitality, from Homeric parallels through the nineteenth-century novel's interest in self-identity, to the implications of the limits of knowledge and recognition of otherness. It also assesses the novella's neo-Victorianism as a literary reimagining of the nineteenth-century world and examines its receptiveness to a post-structuralist questioning of traditional notions of hospitality.